2014
DOI: 10.1002/nbm.3239
|View full text |Cite
|
Sign up to set email alerts
|

Six fucose‐α(1–2) sugars and α‐fucose assigned in the human brain using in vivo two‐dimensional MRS

Abstract: A growing body of literature has indicated that fucose-α(1-2)-galactose sugars are implicated in the molecular mechanisms that underlie neuronal development, learning and memory in the human brain. An understanding of the in vivo roles played by these terminal fucose residues has been hampered by the lack of technology to non-invasively monitor their levels in the human brain. We have implemented in vivo two-dimensional MRS technology to examine the human brain in a 3-T clinical MR scanner, and report that six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 29 publications
2
37
1
Order By: Relevance
“…Changes in fucose levels (0700–1700) is also worth mentioning, as we noted an increase in fucose in the afternoon (+23.4%). The glycosylation of various sugars is complex and a previous 2D L‐COSY study identified six different types of fucose residues with variation from person to person according to age and health state . We did not find any diurnal variation with GABA concentrations and this validates the study by Evans et al that time of day had no bearing on GABA levels from two brain regions .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Changes in fucose levels (0700–1700) is also worth mentioning, as we noted an increase in fucose in the afternoon (+23.4%). The glycosylation of various sugars is complex and a previous 2D L‐COSY study identified six different types of fucose residues with variation from person to person according to age and health state . We did not find any diurnal variation with GABA concentrations and this validates the study by Evans et al that time of day had no bearing on GABA levels from two brain regions .…”
Section: Discussionsupporting
confidence: 88%
“…The glycosylation of various sugars is complex and a previous 2D L-COSY study identified six different types of fucose residues with variation from person to person according to age and health state. 30 We did not find any diurnal variation with GABA concentrations and this validates the study by Evans et al that time of day had no bearing on GABA levels from two brain regions. 19 GSH, Hca, and lipids/MM are other metabolites that showed significant variations during the 10-hour period from morning to evening.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, 2D L‐COSY still remains the technique of choice for the detection of J‐coupled metabolite and improved spectral dispersion . Low concentration metabolites such as GABA, GSH, glucose, and fucose have been found to be biomarkers for many neurological disorders . 2D L‐COSY has a great potential in detecting these important low concentration metabolites with higher confidence.…”
Section: Discussionmentioning
confidence: 99%
“…27 Low concentration metabolites such as GABA, GSH, glucose, and fucose have been found to be biomarkers for many neurological disorders. 2,11,42,44,45 2D L-COSY has a great potential in detecting these important low concentration metabolites with higher confidence.…”
Section: Discussionmentioning
confidence: 99%
“…This is due particularly in light of the results of a number of studies indicating a role for fucosylation in cognitive function, learning, and memory Matthies et al, 1996;Murrey and Hsieh-Wilson, 2008;Mountford et al, 2014). L-Fucose is highly enriched at neuronal synapses (Murrey et al, 2006), where the majority of the fucosylated glycoconjugates exist as complex Nlinked glycoprotein structures.…”
Section: Introductionmentioning
confidence: 97%